Critical care units' catecholamine drugs preparation and administration protocol for adults in north and middle West Bank hospitals : " facilitations and obstacles ". - Zeinat Jarawan; Mona Sharar; Raneen Amer; Shaheera Ismail; Aya Sharar (My University, 2019)
Background: Catecholamine is a group of drugs which mostly used in critical care units, include Dopamine, Dobutamine, Epinephrine and Nor-epinephrine. Catecholamine plays an important role in body's physiological response to stress, so it is essential to prepare and administer it based on a standard protocol. Aim: To identify if intensive care units in north and middle west bank hospitals use the standard protocol in preparation and administration of catecholamine. Methodology: A quantitative descriptive design because our aims tend to describe the variables, time and cost efficient. The study includes 211 nurses from different sites (Nablus, Ramallah, Oalqiliah, Tulkerm, Sulfite, Jenin ) hospitals in critical care units. Results and Conclusion: Study results show that 82.5% of nurses agree with the availability of catecholamine protocol, 81% of them adhered to the protocol implementation. Even though study results found that most of nurses agree with the availability of catecholamine protocol, nurses thought that they know and understand how to implement the protocol and study results show that they don’t and that presented in section seven from the questionnaire.
Keywords: Protocol, ICU, CCU, Critical Care Units, Catecholamine, Dopamine, Dobutamine , Epinephrine and Nor-epinephrine